Strength Recovery of Lightweight Concrete under Elevated Temperature - Barbhuiya, Salim; Lo, T.; Memon, S.; Nikraz, Hamid (Trans Tech Publications, Switzerland, 2014)
This research is aimed at investigating the effect of elevated temperature, curing duration and curing methods on the strength recovery of lightweight concrete. Concrete specimens were subjected to elevated temperatures ranging from 300 to 600°C in a controlled heating environment. The specimens were subjected to three types of curing conditions: continuous water curing at 27°C, curing in a relative humidity of 95% at 27°C and curing in water at 60°C for three days and then curing in water at 27°C. The curing duration ranged from 7 to 56 days. The results indicated that there-curing of concrete for the recovery of compressive strength is most effective in the temperature range from 300 to 500°C. For temperatures outside the range of 300 to 500°C, re-curing was either not effective or had limited application.